Taxpayers in business - Richard Naidu (Asia Pacific Network, 1999)
'Whether the Post retains editorial independence remains to be seen. The Post's past editorial policy has supported media independence. Perhaps the first ominous sign is the Post's lack of editorial comment on the deal.'